Analisis Performa Struktural Material SAPH440 untuk Rangka Dandori Dies Mesin Press Industri - -, Ujiburrahman; Boni Sena; Mohamad Zaenudin (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
In the sheet metal forming process within the automotive and heavy machinery industries, the Dandori frame component in the die system plays a crucial role as a compressive load-bearing support. This study aims to analyze the static performance of the Dandori frame structure in a press machine using SAPH440 material. The method employed is the Finite Element Method (FEM) based on SolidWorks software to evaluate displacement, von Mises stress, and the factor of safety parameters under load variations of 1000 kg and 2000 kg. Simulation results show that the maximum deformation is only 0.032 mm, indicating high structural stiffness. The maximum stress recorded is 14.286 MPa, uniformly distributed without excessive concentration, and well below the material's yield strength. Meanwhile, the factor of safety is evenly distributed with a value of 3 throughout the structure, indicating a safe design condition. Overall, the simulation results demonstrate that SAPH440 is a suitable and effective material for use in Dandori die frames under static load applications.